Pelatihan Kitoka bagi Siswa SMPN 2 Pangsid Kabupaten Sidrap - Ihsan, Andi; Saputra, Andi Taslim; Hasbi, Hasbi; Rasul, Rasul; Ramli, Asia (Universitas Negeri Makassar, 2025)
Access to authentic lutes is often a barrier for schools in this region. To address this issue, using Kitoka can be a learning alternative. Kitoka is a musical instrument that can simulate sound and musical playing techniques interactively, making it easier and more engaging for students to learn the kecapi. The use of Kitoka at SMP Negeri 2 Pangsid, Sidrap Regency, is expected to provide a solution for the preservation of local culture by utilizing a new learning model to support the curiosity of school students, serving as a new tool in music art learning with boring teaching methods. This training is intended for students of State Junior High School 2 Pangsid, Sidrap Regency. With the training on using Kitoka thru interactive methods, including demonstration and drill methods, the above problems can be overcome in a more innovative and effective way. Students participate in training activities using the upward and downward picking techniques repeatedly. This plucking technique was then demonstrated to the students so they could practice both techniques. The plucking pattern was taught using the drill method, or by repeatedly playing this technique. Next, the students practiced playing musical notes by performing the song